2017
DOI: 10.1016/j.automatica.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behaviour in the robot rendezvous problem

Abstract: Abstract. This paper presents a natural extension of the results obtained by Feintuch and Francis in [5,6] concerning the so-called robot rendezvous problem. In particular, we revisit a known necessary and sufficient condition for convergence of the solution in terms of Cesàro convergence of the translates S k x0, k ≥ 0, of the sequence x0 of initial positions under the right-shift operator S, thus shedding new light on questions left open in [5,6]. We then present a new proof showing that a certain stronger e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In Feintuch and Francis [1], it is suggested that the Banach space 𝓁 ∞ should be chosen as the state space. The behavior of infinite chains of kinematic points and second-order infinite dimensional systems is considered in the 𝓁 ∞ -framework [1][2][3][4][5]. In Athalye et al [6], there appear infinite dimensional systems whose dynamics is governed by Laurent operators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Feintuch and Francis [1], it is suggested that the Banach space 𝓁 ∞ should be chosen as the state space. The behavior of infinite chains of kinematic points and second-order infinite dimensional systems is considered in the 𝓁 ∞ -framework [1][2][3][4][5]. In Athalye et al [6], there appear infinite dimensional systems whose dynamics is governed by Laurent operators.…”
Section: Introductionmentioning
confidence: 99%
“…In Paunonen and Seifert [7], ergodic theory and C 0 ‐semigroups are used to investigate the asymptotic behavior of the infinite system. The resulting class of systems covers a number of important applications including the robot rendezvous problem [1,3,8] and platoon systems [9–14].…”
Section: Introductionmentioning
confidence: 99%
“…Synchronization phenomena were observed in di erent elds, such as synchronization of oscillators, swarms of birds, schools of sh, and robot rendezvous [1][2][3][4][5]. Synchronization is one of the fundamental aspects of selforganization in networks of systems.…”
Section: Introductionmentioning
confidence: 99%
“…e conventional, bipartite, and cluster consensus problems can be unified in our given weighted consensus frame. (2) To solve weighted consensus problem, the edge-and nodeweighted digraph is adopted to model the interaction topology among agents, by which the distributed protocol to solve the weighted consensus problem is provided. (3) e equivalence between weighted consensus and conventional consensus is established, by which most conventional consensus protocols can be generalized to solve the weighted consensus problem directly.…”
Section: Introductionmentioning
confidence: 99%